'I'd rather die in the middle of a street': Perceptions and expectations of aged care among Forgotten Australians. (17th December 2020) - Browne‐Yung, Kathryn; O'Neil, Diana; Walker, Ruth; Smyth, Alison; Putsey, Peter; Corlis, Megan; Laver, Kate E.; Fernandez, Elizabeth; Cations, Monica
Abstract: Objectives: To explore perceptions and expectations regarding aged care among older Forgotten Australians, informing better ways of delivering safe and inclusive care for this group. Methods: In‐depth interviews were undertaken with sixteen Forgotten Australians to understand their perspectives, hopes and perceived barriers to receiving appropriate aged care. Qualitative data were analysed using Ritchie and Spencer's framework approach. Results: Participants were highly averse to receiving aged care in residential settings, particularly where delivered by religious organisations. Limited perceived opportunities to develop trust and maintain control and independence while managing re‐traumatising situations shaped Forgotten Australians negative perceptions of the aged care system. Participants also spoke of how their lifelong marginalisation could limit their access to choice and quality in aged care. Conclusion: The aged care industry could provide safe and inclusive care by adopting a person‐centred and trauma‐informed model that recognises and addresses the specific needs and challenges of Forgotten Australians.